Closed Loop Supply Chain Under Consignment Stock Partnership - Khan, Zenab (2015)
A Master of Science thesis in Engineering Systems Management by Zenab Khan entitled, "Closed Loop Supply Chain Under Consignment Stock Partnership," submitted in May 2015. Thesis advisor is Dr. Moncer Hariga and thesis co-advisor is Dr. Rami As'ad. Soft and hard copy available.